2010
DOI: 10.3349/ymj.2010.51.5.661
|View full text |Cite
|
Sign up to set email alerts
|

Acute Stress and Chronic Stress Change Brain-Derived Neurotrophic Factor (BDNF) and Tyrosine Kinase-Coupled Receptor (TrkB) Expression in Both Young and Aged Rat Hippocampus

Abstract: PurposeThe purpose of this study is to explore the dynamic change of brain-derived neurotrophic factor (BDNF) mRNA, protein, and tyrosine kinase-coupled receptor (TrkB) mRNA of the rat hippocampus under different stress conditions and to explore the influence of senescence on the productions expression.Materials and MethodsBy using forced-swimming in 4℃ cold ice water and 25℃ warm water, young and aged male rats were randomly divided into acute stress (AS) and chronic mild repeated stress (CMRS) subgroups, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
63
1
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(74 citation statements)
references
References 56 publications
4
63
1
4
Order By: Relevance
“…Direct infusion of BDNF leads to recovery of behavioral deficits in depressed rats (Sairanen et al 2005;Siuciak et al 1997) and chronic administration of antidepressants increases BDNF levels in cortical and hippocampal areas (Nibuya et al 1995;Russo-Neustadt et al 2001). Conversely, long-term stress reduces hippocampal BDNF, which, by contributing to the atrophy and even the death of pyramidal neurons in the hippocampus, may play a role in stress-related psychiatric illnesses (Bennett and Lagopoulos 2014;Monteggia et al 2007;Shi et al 2010;Smith et al 1995). In human, a post-mortem study of depressed patients reported a reduction in BDNF expression (Karege et al 2005) and polymorphisms of BDNF gene were associated with increased susceptibility to depression (Neves-Pereira et al 2002;Sen et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Direct infusion of BDNF leads to recovery of behavioral deficits in depressed rats (Sairanen et al 2005;Siuciak et al 1997) and chronic administration of antidepressants increases BDNF levels in cortical and hippocampal areas (Nibuya et al 1995;Russo-Neustadt et al 2001). Conversely, long-term stress reduces hippocampal BDNF, which, by contributing to the atrophy and even the death of pyramidal neurons in the hippocampus, may play a role in stress-related psychiatric illnesses (Bennett and Lagopoulos 2014;Monteggia et al 2007;Shi et al 2010;Smith et al 1995). In human, a post-mortem study of depressed patients reported a reduction in BDNF expression (Karege et al 2005) and polymorphisms of BDNF gene were associated with increased susceptibility to depression (Neves-Pereira et al 2002;Sen et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Hippocampal pyramidal neurons secrete NGFs in response to stress which correspond to HPA axis activity (123,124), and also TrkB, the receptor for BDNF is found to be co-localized with glucocorticoid receptor (GR) and having mutual influence on each other's signalling in these neurons (122). A study by Lambert et al has shown in primary rat cortical neurons that BDNF induces structural change at GR gene (phosphorylation at serine 155 and 287) and causes significant change in its transcriptome (125).…”
Section: Fig 2 Stress Induced Hpa Axis Mediated Disruption In Ngfs mentioning
confidence: 99%
“…BDNF/TrkB signal transduction pathways may also participate in the process of learning and memory during chronic stress (Li et al, 2007). A study indicates that chronic mild repeated stress results in decrease of BDNF mRNA and protein (Shi et al, 2010). Therefore, we have designed an investigation to study the neuroprotective effect of herbaceous cognitive enhancer, Centella asiatica, on serum BDNF concentration, that is believed to play an important role in learning and memory process, in chronic stressed-rats.…”
Section: Introductionmentioning
confidence: 99%